A PRAGMATIC CRITICAL STUDY OF DECEPTION IN WILLIAM SHAKESPEARE’S MACBETH - Kadhim, Saad Badi; Hassan, Dhuha Ismail Khalil (Journal of Social Science, 2026)
Objective: This study explores the manifestation of deceit in Shakespeare’s Macbeth through pragmatic and critical discourse analysis, with specific aims of identifying the types of deception employed, uncovering the thematic topics that fuel persuasive deceit, and proposing an eclectic model for categorizing deceptive utterances based on Fairclough’s (1989) framework. Method: Employing a qualitative design, the research systematically examines textual evidence from the play, applying discourse-analytic techniques to classify and interpret deceptive strategies within the dramatic context. Results: The analysis reveals that directive speech acts dominate the early stages of deception, with prosperity, throne, pride, and power as recurring themes, while overstatements and violations of the quality maxim emerge as the most frequent forms of deceit. The study also indicates that concealment is scarcely observed, and speech acts with dual pragmatic force are rare. Novelty: By integrating Fairclough’s critical discourse model into an eclectic framework, this research advances a distinctive approach to literary pragmatics, offering new insights into how rhetorical deception is constructed and functions in shaping characters’ ideologies and the tragic trajectory of Shakespeare’s play.